Synthesis, spectroscopic characterizations, photophysical properties and DFT studies of a novel iridium(III) complex containing 2-(2-butoxy-4-fluorophenyl) pyridine ligand - Noorshida Mohd Ali (Tanjung Malim, 2023)
Synthesis, spectroscopic characterizations, photophysical properties and DFT studies of a novel iridium(III) complex containing 2-(2-butoxy-4-fluorophenyl) pyridine ligand by Noorshida Mohd Ali